'I usually never got involved': understanding reasons for secondary students with visual impairments leaving mainstream schooling in Germany. Issue 2 (4th March 2022) - Giese, Martin; Greisbach, Michaela; Meier, Michelle; Neusser, Theresa; Wetekam, Nino
ABSTRACT: The study aims for identifying the driving forces that lead German children with VI to switch from mainstream schooling to special schooling. The results are intended to provide more understanding from the perspective of these students about how school settings for students with and without visual impairment can be designed with as few barriers as possible to meet these students' specific needs. Six female and four male students, who have been schooled inclusively during their school career and then made the decision to be educated in the upper Gymnasium (grammar school) classes at a special school participated in the present study. It is apparent that all of the students had extensive experiences of exclusion in mainstream schooling. The results show perceived barriers on the school and instructional-organisational level, as well as problems on the level of social-emotional relationships with fellow students and teachers. It is evident that the perception of barriers increases with the length of school attendance and that private supplementary involvement is described as the most important resource. In consideration of the results a two-level model of school inclusion barriers for children with VI is presented.